Development of Hazard Identification, Risk Assessment, and Opportunities (HIRAO) Report in ISO 45001:2018 for Segmental Box Girder (SBG) Installation in the KVLRT3 Project - Mohd Nasir, Nurul Nasirah Binti; Mahyeddin , Mohd Eizzuddin Bin (Progress in Engineering Application and Technology, 2022)
The construction sector is associated with various accidents and fatal injuries. These occupational accidents are caused by numerous factors such as lack of supervision, working above live traffic, mechanical malfunction, working at height, and unexpected movement of cargo or load during lifting due to the wind. In this study, the Hazard Identification, Risk Assessment, and Opportunities (HIRAO) report was developed to analyze the hazards involved in the job sequences of SBG installation by the balanced cantilever method using a crane. The HIRAO report is produced by identifying the hazards involved in the activities using all the source information such as workplace inspection, injuries, illness, incident, accident report, team consultation, and employee feedback and observation. The risk associated was identified and analyzed by qualitative method to observe the level of the risk-based on previous actual accidents that happened in the construction industry. The opportunities for every hazard involved in the job sequences also were identified to complete the HIRAO report as one of the elements of ISO 45001:2018 based on the SWOT analysis constructed. From the current risk assessment, the additional risk control was measured for the future project to reduce the risk at once it will give opportunities to prevent or minimize accidents at the workplace. The HIRAO report produced will be proposed to the company AlKauthar Kinematics as a part of the element in ISO 45001:2018. However, the ISO 45001:2018 cannot be implemented yet due to the cost that will be spent.